Berkaca NU dan Muhammadiyah dalam Mewujudkan Nilai-Nilai Moderasi Islam di Indonesia - Amru Almu’tasim (TARBIYA ISLAMIA : Jurnal Pendidikan dan Keislaman, 2019)
Maintaining the moderation of Islam in Indonesia is a must because it is a command of the Qur'an. Didin Hafidhuddin said; Moderate does not mean that all religions are equal in line with the Ministry of Religion and MUI. Collaborative Cadre of Moderate Missionaries Muhammadiyah moderate and not excessive "Not too right (extreme) and not too left (liberal). This group of moderate wasathons or Muslims, in Ahlussunnah wal Jamaah (Aswaja) terms are called sawadh al-a'zham, or the largest group, the Aswaja group. It is this group that is embraced by most Muslims in Indonesia, which has so far maintained the country's sovereignty. The trend that is being echoed in the world today is the enthusiasm of Muslims to maintain this moderation, namely moderate Islam. So it is important, because it is too right (extreme) to only see things from a black and white, halal and haram angle, which sometimes when applied in a pluralistic society is not quite right, "sure the goals of all Islamic groups in Indonesia are the same, but when delivered in a way right and more flexible, it is felt to have more impact compared to the extreme values ??of moderation of Islam that is actually what is currently needed by the world and needs to be used as a reference for sawad al-a'zham or the Muslim group, Aswaja and this is very in accordance with The Koran commands The problem is that there are opinions of Muslims who think that if there is something that is not in accordance with Islam, everything needs to be replaced, even though there are principles of fiqh that view the business and its way, as long as the benefits for Muslims must be accepted.